The Impact of Organizational Justice, Self-Efficacy and Teachers Performance: The Mediating Role of Internal Motivation - Sopiah, Sopiah; Mamang Sangadji, Etta; Shandy Narmaditya, Bagus (Pedagogika, 2023)
This study examines the impact of organizational justice and self-efficacy on teachers’ performance in Indonesia and the role of internal motivation. Using path analysis, the findings indicate that both organizational justice and self-efficacy can affect teacher performance and correlate with internal motivation. Additionally, internal motivation plays a role as a partial mediating relationship between organizational justice and teacher performance, as well as mediating self-efficacy and teacher’s performance.